Prospective 5-year survival rate data following open-wedge valgus high tibial osteotomy - Bode, Gerrit; von Heyden, Johanna; Pestka, Jan; Schmal, Hagen; Salzmann, Gian; Südkamp, Norbert; Niemeyer, Philipp (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2015)
Purpose Open-wedge high tibial osteotomy using internal plate fixation is a well-established and frequently performed treatment option for the management of medial compartment osteoarthritis (OA) in the young and active patients. The present study provides survival rate and functional outcome preoperatively and after 6, 12, 24, 36 and 60 months following open-wedge high tibial osteotomy. Hypothesis of the authors was high survival rates after 5 years with still remaining satisfying functional results. Methods Sixty-two patients suffering from tibial conditioned knee joint varus deformity and medial compartment OA that underwent high tibial osteotomy using an internal plate fixator (TomoFix™, Synthes) were included. Functional outcome was evaluated prior to surgery and in the further clinical course using standard instruments (IKDC score, Lysholm score). Treatment failure was defined as the need for total knee arthroplasty (TKA). Results Fifty-one patients (mean age 46.8 ± 10.2 years) were available at a mean of 60.5 (SD ± 2.5) months (follow-up rate 82.3 %) postoperatively. Sixty-month IKDC (69.4 % SD ± 18.6) and Lysholm (76.6 SD ± 20.5) improved significantly when comparing with preoperative values (IKDC 44.6 SD ± 17.8; Lysholm 52.1 SD ± 20.8). Two of 51 subjects underwent TKA, resulting in a survival rate of 96 % among those patients followed (51 of 60; 85 %). Overall complication rate was 8.6 %. Conclusion With a survival rate of over 96 % at 5 years, high tibial osteotomy seems to be a reliable treatment option with satisfying clinical outcome. Functional outcome was stable following 60 months. While a delay of the necessity for TKA seems likely with regard to the survival rate demonstrated in this article, possible avoidance needs to be demonstrated by longer follow-up studies. Level of evidence Therapeutic case series, Level IV.